Comparative Analysis of Customer Satisfaction Levels between B2C Business Models on Brand Equity in the Culinary Industry - Khairunnisah, Noni Antika; Ahmad, Ahmad; Maesarah, Maesarah (Business Management, 2025)
Abstract. This research intends to analyze the comparison of customer satisfaction levels between B2C business models and their influence on brand equity in the culinary industry. Urgency This research is based on intense competition in the culinary industry, where customer satisfaction and brand equity are the keys to business success. B2C models that focus directly on consumers have different satisfaction dynamics compared to other business models, so they require in-depth analysis regarding their impact on brand equity. This research uses quantitative methods with a survey approach to collect data from culinary customers interacting with the B2C model. Descriptive and inferential statistical analysis will be used to compare customer satisfaction levels and measure their impact on the dimensions of brand equity such as brand awareness, brand associations, perceived quality, and brand loyalty. This research will also identify the dominant factors that influence customer satisfaction in the B2C context in the culinary industry. The targeted output of this research is the publication of the Sinta 5 journal in the IFI-JEB journal]